Post-COVID-19 Software Development Life Cycle Method Analysis: A Literature Review - Wiguna, Kevin; Wahyuni, Sri; Imelda, Imelda (P3M Politeknik Negeri Bengkalis, 2024)
The evolution of Software Development Life Cycle (SDLC) methods post-COVID-19 has been critical in navigating the changing landscape of software development practices. This study conducted a comprehensive literature review to explain the adaptation and innovation of SDLC methods after the pandemic. It explores the importance of SDLC in information systems development and its role in promoting transparency, quality, and risk management. Leveraging a systematic literature review methodology, this study analyzes a series of studies published from 2021 to 2024, with a focus on SDLC models commonly used post-COVID-19. Despite potential bias in the selection of literature and limitations in time coverage, this study provides valuable insights into the most widely used uses of agile and scrum methodologies in various sectors, including business, education, government, finance, health, employment, and the food industry. This study underscores the importance of understanding the post-pandemic SDLC method landscape and its implications for software development practices. These findings are important for practitioners and researchers looking to navigate the dynamic environment of software development following the COVID-19 pandemic.